Management of shaft of femur fracture in a patient with underlying arteriovenous malformation with an intramedullary nail - Deepak Kumar; Praveen Sodavarapu; K Nikhil Raj; Vishnu Baburaj (Archives of Trauma Research, 2020)
We present a rare case of pathological shaft of femur fracture in an 18-year-old male, with an underlying arteriovenous malformation (AVM). Magnetic resonance imaging showed extensive intraosseous femoral involvement of the vascular malformation, and the canal was deemed to be wide enough for a nail based on the radiograph templates and computed tomography (CT) scan. The patient was given four sessions of stereotactic external beam radiotherapy preoperatively, and closed reduction and internal fixation was performed using a proximal femoral nail without any complications. Radiographic evidence of fracture union was observed at 4 months. Fracture fixation by closed reduction can be either intramedullary fixation or external fixation based on the adequacy of the canal as determined by radiograph and CT scan. Preoperative measures to decrease vascularity such as stereotactic radiotherapy and angiographic embolization can be undertaken to reduce bleeding. A multidisciplinary approach is essential to improve the management of fractures in a patient with AVM.